Novel MOF-based vanadium and 2,2 -bipyridine-4,4 -dicarboxylic acid as phenomenal dye adsorbent and antimicrobial agent - Mohammed Yaseen, Baraa; Altalbawy, Farag M. A.; Jihad Albadr, Rafid; Mohammed Taher, Waam; Alwan, Mariem; Jasem Jawad, Mahmood; Mushtaq, Hiba; Muzammil, Khursheed; Hussein Zwamel, Ahmed (Frontiers in Chemistry, 2025)
In this study, a new MOF (metal-organic framework) based on vanadium and 2,2-bipyridine-4,4-dicarboxylic acid (V/BP-MOF) was synthesized. Synthesized V/BP-MOF was introduced as a strong adsorbent of Congo Red (CR) and an effective agent in eliminating microbial species. In the investigation of CR absorption activity, several factors such as concentration of V/BP-MOF, pH, time, and temperature were investigated. Antimicrobial evaluations were carried out on Common bacterial strains in wastewater and values of MIC (minimum inhibitory concentration) and MBC (Minimum Bactericidal Concentration) were reported. The V/BP-MOF was confirmed and characterized by EA, EDS, EDS mapping, FT-IR, XRD, TGA, BET, SEM, and TEM. In checking the characteristics of V/BP-MOF, size, specific surface area, and thermal stability were obtained, respectively, 68 nm, 325 m2/g, and 320°C. The highest adsorption of CR, at 94%, was obtained at natural pH, ambient temperature, and after 150 min. In kinetic studies, a correlation coefficient of 0.99 was observed with the pseudo-second-order kinetic model, while in isotherm studies, a correlation coefficient of 0.97 was observed with the Freundlich isotherm model. In the biological evaluations, the best inhibition was against Escherichia coli, and MIC and MBC were observed as 4 μg/mL and 2 μg/mL, respectively. As a general result, V/BP-MOF can be introduced as a potent absorbent agent of CR dye and antimicrobial properties. Therefore, the compound synthesized in this study can be introduced as a suitable option for the wastewater treatment industry, with multiple capabilities including the removal of chemical pollutants and pathogenic agents.